Changing the text through explicitation. How trainee interpreters perceive the role of explicitating shifts. (3rd April 2022) - Gumul, Ewa
ABSTRACT: The paper reports on process- and product-oriented analysis of trainee interpreters' motivations in explicitating the translated message and their own perception of the role of such shifts. The research method is self-retrospection triangulated with product analysis (manual comparison of source and target texts). The study aims to find out to what extent the effects produced by explicitations in target texts coincide with the reported motivations of trainee interpreters to perform explicitating shifts. The results show a low level of correspondence between trainee interpreters' motivations in performing explicitations and the actual effect such shifts exert on target texts. Trainees' awareness of the consequences of explicitation appears to be related to the metafunction of such shifts. While the subjects in this study show some degree of awareness how their textual and interpersonal shifts affect the message, very few of them appear to be conscious of the consequences of ideational shifts.